Fasting diets: what are the impacts on eating behaviors, sleep, mood, and well-being? - Hosseini, Elham; Ammar, Achraf; Josephson, Jessica K.; Gibson, Deanna L.; Askari, Gholamreza; Bragazzi, Nicola L.; Trabelsi, Khaled; Schöllhorn, Wolfgang I.; Mokhtari, Zeinab (Frontiers in Nutrition, 2024)
Fasting diets (FDs) have drawn great attention concerning their contribution to health and disease over the last decade. Despite considerable interest in FDs, the effect of fasting diets on eating behaviors, sleep, and mood -essential components of diet satisfaction and mental health-has not been addressed comprehensively. Understanding the critical role that fasting plays in these elements will open up potential treatment avenues that have not yet been explored. The aim of the present paper was to conduct a comprehensive critical review exploring the effects of fasting on eating behaviors, sleep, and mood.There is currently a lack of clarity regarding which fasting option yields the most advantageous effects, and there is also a scarcity of consistent trials that assess the effects of FDs in a comparable manner. Similarly, the effects and/or treatment options for utilizing FDs to modify eating and sleep behaviors and enhance mood are still poorly understood. Further researches aiming at understanding the impacts of various fasting regimes, providing new insights into the gut-brain axis and offering new treatment avenues for those with resistant anxiety and depression, are warranted. Alteration of eating behaviors can have lasting effects on various physiological parameters. The use of fasting cures can underpin ancient knowledge with scientific evidence to form a new approach to the prevention and treatment of problems associated with co-morbidities or challenges pertaining to eating behaviors. Therefore, a thorough examination of the various fasting regimens and how they impact disease patterns is also warranted.